Trabajo en equipo y la productividad laboral de los trabajadores de la jefatura zonal de migraciones Iquitos 2023 - Torres López, Elsa Liliana (2024)
The general objective was to determine the relationship between teamwork and work productivity of the employees of the headquarters at the Iquitos 2023 migration headquarters. The method was designed to be quantitative, non experimental and correlational. The population was made up of 30 workers from the Migration 2023 headquarters in Iquitos, and a sample of 100% of the population was obtained through convenience census sampling. The method was a questionnaire and the instruments were the Sánchez and Baishaul questionnaire and the size of the company (validity = 0.806, reliability = 72.11%). The results showed that teamwork and work productivity have a positive and significant relationship among workers at the Iquitos 2023 Migration District Headquarters. The data were analyzed using the SPSS 26.0 program. The inferential statistical tests were chi-square (X2) and contingency coefficient (CC) with α = 0.05 and 95% confidence level. Results: Of 100.0% (30 people) of employees, 63.3% (19 people) have been involved in teamwork. The same thing happens to 60% (18 people). Employees experienced a temporary decline in work productivity. In conclusion, a significant positive relationship was found between teamwork and work productivity at the Iquitos 2023 Migration District Headquarters, confirmed by the Pearson correlation coefficient (0.766) with significance at the 0.000 level.